Design and analysis wheel and mobility system for robotic arm car - Mohd Suhaimi, Muhammad Aqim (2024)
This project is to design and construct a wheel and mobility system for a robotic arm car to improve the mobility of the conventional robotic arms. The earlier models of robotic arms are usually static; this limits the area in which they can work. This project solves these issues by coming up with a strong and portable mobility system that can work on different terrains. The basic idea is to make a structure that will bear the weight of the robotic arm and make it stable so that it can be used in any area like kindergarten which can help the caregivers as well as be of educational importance. The phases of the project are concept development, designing with the help of SolidWorks, and engineering evaluation. This paper also identified initial concepts which were analyzed using a morphological chart and a Pugh chart to select the best concept. Therefore, stress, strain, and displacement analysis were performed to ensure the structural efficacy of the design. The structure construction include laser cutting, and assembling of various elements from affordable materials such as acrylic and aluminum. The expected outcome is a versatile, and can operate seamlessly on any surface and in the process perform useful tasks in the day life and have educational value. This project also seeks to enhance the working of the robotic arms while at the same time encouraging young students to engage in robotics and engineering to enhance STEM education.